Measurement of the W boson mass with the D0 detector - Abazov, V; Abbott, B; Acharya, B; Adams, M; Adams, T; Alexeev, G; Alkhazov, G; Alton, A; Alverson, G; Aoki, M; Askew, A; Sman, B; et al. (2012)
We present a measurement of the W boson mass using data corresponding to 4.3fb -1 of integrated luminosity collected with the D0 detector during Run II at the Fermilab Tevatron pp̄ collider. With a sample of 1677394 W→eν candidate events, we measure M W=80.367±0. 026GeV. This result is combined with an earlier D0 result determined using an independent Run II data sample, corresponding to 1fb -1 of integrated luminosity, to yield M W=80.375±0.023GeV. © 2012 American Physical Society.